Phosphole‐ and Benzodithiophene‐Based Copolymers: Synthesis and Application in Organic Photovoltaics. Issue 10 (22nd October 2013) - Matano, Yoshihiro; Ohkubo, Hiroshi; Miyata, Tetsushi; Watanabe, Yusuke; Hayashi, Yukiko; Umeyama, Tomokazu; Imahori, Hiroshi
Abstract: Two kinds of phosphole‐ and benzodithiophene‐based copolymers bearing P V =O or P V =NSO2 C8 H17 functions were prepared by Pd–CuI‐promoted Stille coupling reactions, and their optical and electrochemical properties were investigated. Bulk heterojunction organic photovoltaic devices comprised of the new P, S‐bridged copolymers and (6, 6)‐phenyl‐C71‐butyric acid methyl ester (PC71 BM) exhibited power conversion efficiencies of up to 0.65 % under AM1.5 irradiation at 100 mW cm –2 . Abstract : Novel conjugated copolymers containing alternating benzodithiophene (electron donor) and phosphole (electron acceptor) units were prepared as low‐bandgap sensitizers for bulk heterojunction organic photovoltaic devices. The devices comprised of the new donor–acceptor copolymers and (6, 6)‐phenyl‐C71‐butyric acid methyl ester (PC71 BM) exhibited power conversion efficiencies of up to 0.65 %.